Safety of Topical Mometasone Furoate 0.1% Cream vs Topical Tacrolimus 0.03% Ointment in the Treatment of Atopic Dermatitis (Medicine Today, 2025)
Introduction: Atopic dermatitis (AD) is an itchy, chronic, or chronically relapsing, inflammatory skin condition, affecting between 10% and 20% of children and 1% and 3% of adults. Atopic dermatitis causes significant physical, psychological and social distress. The prevalence of AD has increased steadily over the last 30 years. Topical steroids and calcineurin inhibitors are the current standard for topical anti-inflammatory therapy. Mometasone furoate cream 0.1% is a medium potency corticosteroid, effective in the treatment of atopic dermatitis in children. Materials and Methods: A clinical trial was conducted from September 2021 to February 2022 to compare the safety of mometasone furoate and tacrolimus in the treatment of Atopic Dermatitis. Patients of Atopic dermatitis attending outpatient department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka were the study population. Patients of atopic dermatitis diagnosed clinically and age more than 2 years were included in the study. Results: In this study, 73.33% of mometasone furoate treated patient and 60% of tacrolimus treated patients did not experience any side effects. Side effects recorded in group A were burning sensation (13.3%), dry skin (6.7%), Desquamation (3.3%) and irritation (3.3%) and in group B were burning(10.0%), dry skin (13.3%), desquamation (10.0%), irritation (3.3%) and erythema (3.3%) (p>0.05). Conclusion: In the light of the findings of the study we conclude that each of the treatment of mometasone furoate and tacrolimus is individually safe in the treatment of atopic dermatitis. The safety and tolerability of mometasone furoate 0.1% is almost same as that of tacrolimus in the treatment of atopic dermatitis.Medicine Today 2025, Vol.37 (1): 14-18